2013
DOI: 10.1111/his.12172
|View full text |Cite
|
Sign up to set email alerts
|

Secretory carcinoma of the breast and its histopathological mimics: value of markers for differential diagnosis

Abstract: In this study, we propose a panel of four markers (ETV6 rearrangement, amylase, α-lactalbumin and adipophilin) for distinguishing SC, ACCA, CHC and IDC. This simple but robust panel will serve pathologists well as a practical guide for reaching an appropriate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 37 publications
2
38
0
4
Order By: Relevance
“…HER2neu status was only reported in 32 SBC patients of whom 31 were negative. These findings are similar to studies by Li et al and Osaka et al . Why earlier and smaller studies found almost exclusively hormone receptor negativity while this larger study from numerous CoC‐approved institutions found many hormone receptor positive SBCs is not clear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HER2neu status was only reported in 32 SBC patients of whom 31 were negative. These findings are similar to studies by Li et al and Osaka et al . Why earlier and smaller studies found almost exclusively hormone receptor negativity while this larger study from numerous CoC‐approved institutions found many hormone receptor positive SBCs is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…All cases showed positive staining for S‐100 protein and mammaglobin . A recent study by Osaka et al found secretory breast cancer to be positive for S‐100, lysozyme and a‐lactalbumin, and to show vacuolar staining of adipophilin . The abundant secretion and similar growth pattern was also seen in metastatic axillary lymph nodes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The immunohistochemical features of cases included in this study have been previously described (9, 12), apart from immunohistochemical analysis using antibodies against lysozyme in three MGA cases (MGA4, MGA5 and MGA8), which was performed as previously described (12), with a polyclonal anti-lysozyme antibody (Ventana) using the CC1 mild pretreatment program on a Benchmark XT autostainer (Ventana). Lysozyme was considered positive if cytoplasmic staining was observed in >1% of tumor cells (19). Positive and negative controls were included in each slide run.…”
Section: Methodsmentioning
confidence: 99%
“…AcCCs of the breast are extremely rare. Only 39 cases have been described in the English literature to date, usually as case reports or small case series . In addition to immunoreactivity for serous differentiation markers, AcCCs of the breast have been reported to display a triple‐negative phenotype; interestingly, however, at variance with the common forms of triple‐negative breast cancer (TNBC), breast AcCCs are reported to have indolent clinical behaviour …”
Section: Introductionmentioning
confidence: 99%